2015
DOI: 10.1134/s1021443715050192
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid and its role in the structure and functions of plant cell membranes

Abstract: The content of palmitic acid (PA) in the fractions of plant lipids of different polarity were investi gated. The following relationship was revealed: when polarity of lipid fraction rose, the content of PA in total fatty acids of this fraction increased. It was shown that in a number of consecutive extracts of total lipids iso lated from plant tissue with the same solvent each next extract containing more tightly bound lipids carries more PA. Predominance of this fatty acid within high polar lipids that may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…The fifth is the compound n-hexadecanoic acid or better known as palmitic acid (PA). PA is the most common saturated fatty acid found in plants (Zhukov, 2015). The presence of AP in B. macrophylla fruit was also reported by Rajan & Bhat (2017) with an analysis using GC-MS.…”
Section: Figure 1 Gas Chromatogram Of Bouea Macrophylla Fruit Juicesupporting
confidence: 68%
“…The fifth is the compound n-hexadecanoic acid or better known as palmitic acid (PA). PA is the most common saturated fatty acid found in plants (Zhukov, 2015). The presence of AP in B. macrophylla fruit was also reported by Rajan & Bhat (2017) with an analysis using GC-MS.…”
Section: Figure 1 Gas Chromatogram Of Bouea Macrophylla Fruit Juicesupporting
confidence: 68%
“…Dodecanoic acid, detected only in M02 and WB06 PABs, derives from pomegranate seeds [ 63 ], and it has been found in small amounts in pomegranate juice and in higher concentrations in pomegranate wine and vinegar [ 57 ]. Hexadecanoic acid is considered to be the most common saturated fatty acid in plants and has been related to the crystalline structure of plant cell membranes [ 64 ]. However, in the present study, it was detected only in SN9 and M02 samples at low concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…These results show that the membrane lipid metabolism pathway is indispensable for rice to adapt to cold conditions. Several recent studies have also shown that membrane lipid remodeling can modulate lipid composition, fatty acyl group unsaturation, and membrane fluidity, which have been developed as a key strategy for plants to adapt to low temperature stress [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%